CO adsorption on the calcite(10.4) surface: a combined experimental and theoretical study. Issue 13 (9th July 2020) - Hafshejani, Tahereh Mohammadi; Wang, Weijia; Heggemann, Jonas; Nefedov, Alexei; Heissler, Stefan; Wang, Yuemin; Rahe, Philipp; Thissen, Peter; Wöll, Christof
Abstract : Information on structural, chemical and physical properties of natural cleaved (10.4) calcite surfaces was obtained by a combined atomic force microscopy and infrared study using CO as a probe molecule under ultrahigh vacuum conditions. Abstract : Detailed information on structural, chemical, and physical properties of natural cleaved (10.4) calcite surfaces was obtained by a combined atomic force microscopy (AFM) and infrared (IR) study using CO as a probe molecule under ultrahigh vacuum (UHV) conditions. The structural quality of the surfaces was determined using non-contact AFM (NC-AFM), which also allowed assigning the adsorption site of CO molecules. Vibrational frequencies of adsorbed CO species were determined by polarization-resolved infrared reflection absorption spectroscopy (IRRAS). At low exposures, adsorption of CO on the freshly cleaved (10.4) calcite surface at a temperature of 62 K led to the occurrence of a single C–O vibrational band located at 2175.8 cm −1, blue-shifted with respect to the gas phase value. For larger exposures, a slight, coverage-induced redshift was observed, leading to a frequency of 2173.4 cm −1 for a full monolayer. The width of the vibrational bands is extremely small, providing strong evidence that the cleaved calcite surface is well-defined with only one CO adsorption site. A quantitative analysis of the IRRA spectra recorded at different surface temperatures revealed a CO binding energy of −0.31 eV. NC-AFM data acquired at 5 K for sub-monolayer CO coverage reveal single molecules imaged as depressions at the position of the protruding surface features, in agreement with the IRRAS results. Since there are no previous experimental data of this type, the interpretation of the results was aided by employing density functional theory calculations to determine adsorption geometries, binding energies, and vibrational frequencies of carbon monoxide on the (10.4) calcite surface. It was found that the preferred geometry of CO on this surface is adsorption on top of calcium in a slightly tilted orientation. With increased coverage, the binding energy shows a small decrease, revealing the presence of repulsive adsorbate–adsorbate interactions.